2010
DOI: 10.1111/j.0105-2896.2009.00886.x
|View full text |Cite
|
Sign up to set email alerts
|

Langerhans cells and more: langerin‐expressing dendritic cell subsets in the skin

Abstract: SummaryLangerhans cells (LCs) are antigen-presenting dendritic cells (DCs) that reside in epithelia. The best studied example is the LC of the epidermis. By electron microscopy, their identifying feature is the unique rod-or tennis racket-shaped Birbeck granule. The phenotypic hallmark is their expression of the C-type lectin receptor langerin/CD207. Langerin, however, is also expressed on a recently discovered population of DC in the dermis and other tissues of the body. These 'dermal langerin + dendritic cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
359
0
18

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 366 publications
(388 citation statements)
references
References 217 publications
11
359
0
18
Order By: Relevance
“…They include (i) a side-by-side comparison of the phenotypes, gene expression programs and proteomes [44,45] [1,2]. pDC detect RNA and DNA from viruses and RNA/DNA/ immunocomplexes through two endosomal sensors, TLR7 and TLR9, respectively, both of which induce secretion of IFN-I through the MyD88-IRF7 signaling pathway [3][4][5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They include (i) a side-by-side comparison of the phenotypes, gene expression programs and proteomes [44,45] [1,2]. pDC detect RNA and DNA from viruses and RNA/DNA/ immunocomplexes through two endosomal sensors, TLR7 and TLR9, respectively, both of which induce secretion of IFN-I through the MyD88-IRF7 signaling pathway [3][4][5].…”
Section: Discussionmentioning
confidence: 99%
“…The functional specialization existing among skin DC subsets is specified in the boxes. All skin DC subsets are capable of inducing delayed type hypersensitivity reactions provided that they have been exposed to the inducing agent [1,5,56]. In addition, CLN contain LT-DC that correspond to the CD8a 1 , the CD11b 1 and the pDC subsets.…”
Section: Presentation Of Pathogen-derived Antigens To T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intradermal administration of Ags is used both to induce responses (as in vaccination) and to monitor immune memory (as in delayed type hypersensitivity tests) as well as in attempts to induce Ag specific tolerance (1,2). The immense potential of the dermal route has been underlined in recent years by the discovery that the epidermis and upper dermis not only have a very high density and wide variety of APCs (3,4) but also a large previously underappreciated reservoir of resident T cells, twice as large as the blood pool (5). This reservoir is polyclonal and in contrast to the blood or lymph node (LN) contains almost exclusively T cells of memory phenotype (6).…”
mentioning
confidence: 99%
“…This fact is important as recent studies have revealed the existence of subsets of Langerin (? ), non-Langerhans dendritic cells, especially in the dermis [4,5]. Langerhans cell histiocytes less often express maturation associated antigens such as CD83 compared to other types of myeloid derived dendritic cells [6,7].…”
Section: Fine Needle Aspiration and Biopsymentioning
confidence: 99%